Marketing management in entrepreneurial activity: strategical aspect - Shyshkin, Viktor; Onyshchenko, Oksana; Zevenko, Dmytro; Bilyk, Oleksandr (Management and Entrepreneurship: Trends of Development, 2023)
The article aimed at determination of the marketing management place and role in the business activities of modern enterprise. Different approaches of Ukrainian and foreign scientists to the «marketing management» term definition have been analyzed. It was determined that enterprises` marketing activities are aimed at establishing the current and, most importantly, strategical goals of the firm. It is noted that effective marketing management is one of the key factors of enterprise development, which allows business to obtain significant competitive advantages and promptly respond to challenges of external environment.It was determined that the effective marketing management model should be based on a systemic approach, which involves presenting marketing as an open system, which is strongly influenced by factors of the internal and external environment. It is noted that the modern enterprise marketing strategy is a component of its general strategy, which is formed on the basis of the marketing environment factors analysis.JEL Classification: M 13, M 31.